CZECH NATIONAL STRATEGY OF DEVELOPMENT OF INTELLIGENT TRANSPORT SYSTEMS AND LINKED ACTIVITIES (Perner's Contacts, 2021)
The article presents topical news on intelligent transport systems policy, strategy, and linked activities in the Czech Republic. It introduces historical background, relation to other documents, and current development in 2021. The Strategy of Development of Intelligent Transport Systems 2021-2027 with a View to 2050 (in force since January 2021) is the core document. The strategy is introduced by its context, methodology and structure of the content. Focus on coming years is included in this article, too: essential support for the ITS policy brings the online ITS Library (https://www.its-knihovna.cz), a knowledge database, described here with its certain parts and space for supportive tools. The tools enable to manage information on implementation progress, selected progress indicators and monitoring of ITS data quality, expressed by data conformance testing and publishing. The conclusion chapter gives a general overview on implementation of the Strategy and the ITS Library in the future.